2013
DOI: 10.3390/agronomy3010059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Previous Crop Management, Fertilization Regime and Water Supply on Potato Tuber Proteome and Yield

Abstract: There is increasing concern about the sustainability and environmental impacts of mineral fertilizer use in agriculture. Increased recycling of nutrients via the use of animal and green manures and fertilizers made from domestic organic waste may reduce reliance on mineral fertilizers. However, the relative availability of nutrients (especially nitrogen) is lower in organic compared to mineral fertilizers, which can result in significantly lower yields in nutrient demanding crops such as potato. It is therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…rotation designs, irrigated or non-irrigated crop production, and level and type of animal manures used) and/or (2) focused on different crop species. This is not surprising as both genetic and environmental/agronomic factors are known to affect the concentrations of N, , , proteins, sugars, antioxidants/(poly)phenolics, Cd and pesticides in crops ( 7 , 9 12 , 20 , 47 52 , 62 ) . However, due to the lack of detailed information on agronomic and pedo-climatic background conditions in most of the available literature, it is currently not possible to quantify the relative contribution of genetic and environmental/agronomic sources of variation.…”
Section: Discussionmentioning
confidence: 99%
“…rotation designs, irrigated or non-irrigated crop production, and level and type of animal manures used) and/or (2) focused on different crop species. This is not surprising as both genetic and environmental/agronomic factors are known to affect the concentrations of N, , , proteins, sugars, antioxidants/(poly)phenolics, Cd and pesticides in crops ( 7 , 9 12 , 20 , 47 52 , 62 ) . However, due to the lack of detailed information on agronomic and pedo-climatic background conditions in most of the available literature, it is currently not possible to quantify the relative contribution of genetic and environmental/agronomic sources of variation.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews/meta-analyses and long-term field experiments have found that yields in organic farming systems are between 10 and 25% lower than the yield in intensive conventional production systems [14][15][16][17][18][19][20][21]. However, the results from a long-term farming system comparison in the Netherlands suggest that the yield gap between organic and conventional farming diminishes over time, and that this coincides with higher nutrientuse efficiency and "spatial stability" in the organic system [17].…”
Section: Effect Of Agronomic Practices On Crop Yield Health and Nutritional Qualitymentioning
confidence: 99%
“…Only a limited number of microbial or plant extract-based and mineral (i.e., S-based and Cu-based) plant protection products are available for organic farmers [13]. Moreover, organic and non-organic production differ in respect to fertilisation protocols (organic vs. mineral synthetic fertilizers) as well as crop rotation systems [15,16]. Such contrasting practices applied in organic and non-organic systems may have an impact on yield, but also on plants' metabolism, which leads to differences in the crops' composition.…”
Section: Introductionmentioning
confidence: 99%